Pembelajaran Menulis Teks Biografi “Joko Widodo” melalui metode Project Base Learning pada Siswa Kelas VIII SMP Negeri 4 Ranoyapo - Ivanda Pendong; Intama Jemy Polii; Oldie Stevie Meruntu (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of Project-Based Learning in teaching biography writing, focusing on the figure of Joko Widodo among eighth-grade students at SMP Negeri 4 Ranoyapo. Employing an empirical descriptive-analytical approach, the research integrates quantitative and qualitative data to capture both learning outcomes and classroom processes. Data were collected through performance tests and structured observations involving 26 students selected through total sampling. The findings indicate a significant improvement in students’ writing competence, as reflected in enhanced organization, language use, and coherence in biographical texts. The learning process also revealed increased student engagement, collaboration, and critical thinking during project execution. Project-Based Learning facilitated contextual learning by connecting instructional content with real-life figures, thereby strengthening both cognitive and affective dimensions of literacy development. The study further highlights the pedagogical relevance of integrating project-oriented strategies within language instruction to promote active learning environments. These results contribute to the growing body of evidence supporting innovative instructional models in enhancing writing proficiency and meaningful learning experiences in secondary education contexts.